Assessing the therapeutic potential of rutin in alleviating symptoms of inflammatory bowel disease: a meta-analysis - Zou, Zhenkai; Zhang, Fanglian; Pan, Zhigang; Xu, Jinyao; Li, Xuanyi; Sun, Xiangjun; Wang, Xufeng; Qin, Feng; Abulizi, Abulikemu; Chen, Qian; Yan, Ruicheng (Frontiers in Pharmacology, 2025)
IntroductionInflammatory bowel disease (IBD) is a chronic, potentially carcinogenic condition with limited treatment options. Rutin may represent a novel approach to treating IBD. Our aim is to conduct a systematic review of rutin, summarize its preclinical effects, demonstrate its efficacy, and provide guidance for future research.MethodsTo systematically evaluate the effectiveness and feasibility of rutin in the treatment of inflammatory bowel disease (IBD) based on published experiments. A literature search up to 2023 on rutin’s effects in IBD was conducted using PubMed, Embase, and Web of Science. Three independent assessors ensured objectivity by selecting and evaluating study quality and extracting data. A meta-analysis was performed using Review Manager 5.3 and STATA 17.0, combining results for a robust evaluation of rutin’s efficacy in IBD treatment.ResultsThe meta-analysis includes nine animal studies with a total of 174 animals. The findings from these studies indicate that rutin has a significant positive impact on various indicators of intestinal disease caused by IBD. Key results include: reduced weight loss, lower disease activity index (DAI), decreased inflammatory markers, reduced oxidative stress markers, increased antioxidant defenses. Its mechanism of action involves anti-inflammatory, antioxidant, inhibition of inflammatory signaling pathways, barrier protection, inhibition of adaptive immune responses, restoration of intestinal permeability, and regulation of microbiota.DiscussionPreclinical evidence suggests that rutin can significantly alleviate the abnormal indicators of intestinal inflammation. In experiments, the performance of rutin in various indicators is very close to existing positive control drugs such as sulfasalazine and budesonide, with similar therapeutic effects. Taken together, this meta-analysis reveal that rutin has the potential to be a feasible drug for the treatment of IBD.Systematic Review RegistrationCRD42024519891.